Pemanfaatan Teknologi Digital dalam Proses Alih Media Arsip Statis di Kantor Depo Arsip Kota Medan - Annisa Rukmana; Abdul Karim Batubara; Kasron M Nasution (Student Scientific Creativity Journal, 2024)
This research discusses the Utilization of Digital Technology in the Media Transfer Process of Static Archives at the Medan City Archives Depot Office. The purpose of this research is to find out the extent to which they utilize current digital technology to transfer static archives. This research method uses a qualitative descriptive approach. By using data collection techniques through interviews, observation and documentation. The informants in this study include the head of the section, archivists and staff responsible for the archive section at the Medan City Archives Depot Office, which have been selected by the researcher according to the criteria of the research subject. The results showed that how the static archive media transfer process is there by scanning the data then the data is processed into a simple form in Microsoft Excel then next to the data there is a link that connects to the original file. The utilization of technology at the Medan City Archives Depot Office is not yet optimal because a lot of equipment such as computers is inadequate and there are still very few human resources who take care of archives.